Coronary artery disease in outpatients with nonvalvular atrial fibrillation: results from the multicenter RAMSES study. Issue 6 (September 2016) - Dogan, Volkan; Başaran, Özcan; Beton, Osman; Tekinalp, Mehmet; Bolat, Ismail; Kalaycioğlu, Ezgi; Aykan, Ahmet Çağri; Taşar, Onur; Şafak, Özgen; Kalçik, Macit; Yaman, Mehmet; Kirma, Cevat; et al.
Abstract : Background: Nonvalvular atrial fibrillation (NVAF) frequently coexists with coronary artery disease (CAD). However, the optimal antithrombotic strategy for patients with concomitant CAD and NVAF is controversial. The aim of this study is to assess the prevalence of CAD with NVAF and to determine antithrombotic treatment options in patients with or without a history of CAD. Methods: ReAl-life Multicenter Survey Evaluating Stroke prevention strategies in Turkey (RAMSES study) was a cross-sectional, multicenter, nationwide observational study carried out in NVAF patients. We studied the clinical data of 6264 Turkish patients participating in the RAMSES study. Demographic properties and antithrombotic therapies were recorded and compared between patients with and without CAD. Results: CAD was present in 1828 (29.2%) of patients with NVAF. Most of the NVAF patients with CAD were men (58%) and comorbid diseases were significantly more common in patients with CAD. Although patients with CAD had higher CHA2 DS2 VASc scores than those without disease (4.1±1.5 vs. 2.9±1.5; P =0.001), they had lower use of oral anticoagulant (OAC) therapy (66.1 vs. 74.4%, P =0.01). Among OAC drugs, warfarin was the preferred medication in patients with CAD (35.4 vs. 30.6%, P =0.01), whereas nonvitamin K antagonist oral anticoagulants were preferred in patients without CAD (40 vs. 34.3%, P =0.01). Patients with CAD required nearly three-fold higher antiplatelet treatment compared with patients without CAD (57.8 vs. 21.4%, P <0.001). Conclusion: CAD affects nearly one-third of patients with NVAF in a real-world setting. Although they merit more aggressive therapy, patients with CAD and NVAF were less likely to receive OAC therapy.